2017
DOI: 10.7448/ias.20.1.21218
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy for HIV in sub‐Saharan Africa and Asia: a comparative analysis of two regional cohorts

Abstract: Introduction: Our understanding of how to achieve optimal long-term adherence to antiretroviral therapy (ART) in settings where the burden of HIV disease is highest remains limited. We compared levels and determinants of adherence over time between HIV-positive persons receiving ART who were enrolled in a bi-regional cohort in sub-Saharan Africa and Asia. Methods: This multicentre prospective study of adults starting first-line ART assessed patient-reported adherence at follow-up clinic visits using a 30-day v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 31 publications
4
64
3
1
Order By: Relevance
“…The age effect was also seen, however, in a previous report from the UHI 5 . These findings contrast with the HIV literature since a large multi-center African study suggested that ART adherence improves with age 26 .…”
Section: Discussioncontrasting
confidence: 99%
“…The age effect was also seen, however, in a previous report from the UHI 5 . These findings contrast with the HIV literature since a large multi-center African study suggested that ART adherence improves with age 26 .…”
Section: Discussioncontrasting
confidence: 99%
“…The regression model showed that female patients were more likely to comply with treatment regimens. The result was in line with various studies in China, 20 sub-Saharan Africa, and Asia, 21 while contradictory results were affirmed in several studies in the USA, 22 British Columbia, and Canada. 23 The heterogeneity across studies, perhaps, could be explained by the sociocultural differences.…”
Section: Discussionsupporting
confidence: 88%
“…Broader dosing intervals are of real potential benefit with current ARV treatments as, when initiated, patient adherence to the offered regimen is imperative, otherwise resistance patterns will rapidly emerge. Unfortunately, for a broad range of reasons that include access limitations, stigma, cost, substance abuse, absorption abnormalities, and comorbidities, patients often do not adhere to regimen recommendations [ 8 , 11 , 46 , 47 ]. While LAP therapeutics will soon become available, they most likely will have a specific niche due, in part, to limitations associated with large injection volumes, injection site reactions, and suboptimal dosing intervals [ 25 , 48 ].…”
Section: Discussionmentioning
confidence: 99%